Hi,

Could anyone run me through getting from this:

$\displaystyle 2\sqrt(6) + 5 = p/q$

to this:

$\displaystyle \sqrt(6) = (p - 5q)/(10q)$

I can't see how it could be done!

Thanks

Printable View

- May 6th 2010, 04:54 PMacebandRe-arrange-ment
Hi,

Could anyone run me through getting from this:

$\displaystyle 2\sqrt(6) + 5 = p/q$

to this:

$\displaystyle \sqrt(6) = (p - 5q)/(10q)$

I can't see how it could be done!

Thanks - May 6th 2010, 04:55 PMAnonymous1
$\displaystyle 2\sqrt{6} + 5 = \frac{p}{q}$

$\displaystyle \implies 2\sqrt{6} = \frac{p}{q} - 5$

$\displaystyle \implies \sqrt{6} = \frac{1}{2}\cdot\frac{p}{q} - \frac{5}{2}$

$\displaystyle \implies \sqrt{6} = \frac{p}{2q} - \frac{5q}{2q}$

$\displaystyle \implies \sqrt{6} = \frac{p-5q}{2q}$